Evaluation of the Adhesion Performance on GNP/Ag/SA Conductive Ink Undergoing Different Curing Time and Temperature - Mohammad Noor, Norida; Salim, Mohd Azli; Masripan, Nor Azmmi; Md. Saad, Adzni; Photong, Chonlatee; Akop, Mohd Zaid (International Journal of Integrated Engineering, 2025)
This research evaluates the adhesion performance of graphene nanoplatelet (GNP)/silver flake (AG)/silver acetate (SA) conductive ink undergoing different curing times and temperatures. The study evaluates how curing parameters, such as temperature and time, impact the resistivity and adhesion strength of the conductive ink. For the preparation of hybrid conductive ink, GNP powder was mixed with ethanol in a beaker. The GNP was sonicated in ethanol for 10 minutes. Then Ag was added to the GNP/ethanol mixture. It proceeded with the sonication for one (1) hour. At room temperature, the mixture powder was poured until it produced a fine powder. Before curing at 250oC for 1 hour, the powder was dripped with organic solvents, 1-butanol, and terpineol and mixed using a thinky mixer machine to form a paste. Next, SA was added to the mixture and sonicated for an additional hour. The solution was heated on a hotplate until the remaining ethanol evaporated. The mixed mixture was then heated in a furnace for one hour to set. The mixture was then pounded until it turned into a fine powder and dripped with  1-butanol and terpineol then mixed using a thinky mixer machine to form a paste. The hybrid conductive ink paste was then printed on copper substrates and was cured at 240°C, 250°C, and 260°C for 4, 5, and 6 hours respectively for each different curing temperature.  A crosshatch adhesion test was done to assess the hybrid conductive ink's adherence to the cooper substrates. In this test, the material's adhesion was evaluated using the ASTM D6677 standard. This standard uses an adhesion scale which ranges from 0B to 5B, where 5B represents the best adhesion. The findings demonstrated that the increased curing temperatures have an adverse effect on the adhesive strength of the conductive ink, highlighting the correlation between curing conditions and adhesion qualities. Future research should focus on the effects of integrating additives or modifying ink composition to improve adhesion qualities during high-temperature curing.